Too late for Flor ; Greed for gold ; The new insecticides [videorecording] - Canlas, Ruben; Lazaro, Cheche (The Probe Team, 1995)
Investigates the government's liability in the execution of Flor Contemplacion; the greed for gold that is dragging Philippine sports and the insects used as the safer and cheaper pesticide for the farmers.